Beam splitting of low-energy guided electrons with a two-sided microwave chip - Zimmermann, Robert; Weber, Philipp; Seidling, Michael; Hommelhoff, Peter (Applied Physics Letters, 2019)
We present a two-layer design and experimental demonstration of a chip-based electron beam splitter working for electron energies up to 200 eV. Beam splitting arises from smoothly transforming the transverse microwave guiding potential from a single-well into a double-well, thereby generating two separated output beams. We discuss future structures for coherent electron beam splitting, which would pave the way for an electron interferometer on a chi
Keywords: chip based electron splitter; quantum microscope; electron microscopy